THE USE OF MODERN EDUCATIONAL METHODS IN IMPROVING THE EFFECTIVENESS OF THE LESSON (Conferencea, 2024)
The main goal of introducing modern methods and innovative technologies into the educational process of primary schools is to achieve optimal overall development of each pupil. In the article highlights of the use of modern educational methods in improving the effectiveness of the lesson in the primary class (on the example of natural sciences).